Implementation of Metabolomic Approaches on Fermented Cereals - Magfiroh, Yani; Hartajanie, Laksmi; Lindayani, Lindayani; Wulandari, Dyah (Journal of Agri-Food Science and Technology, 2025)
Fermentation is a widely utilized food processing technique that enhances sensory characteristics, extends shelf life, and increases product diversity, particularly in cereals. Furthermore, fermentation processes can generate bioactive metabolites that confer various health benefits. Metabolomics is employed to assess changes in the nutritional composition and metabolite profile of fermented cereal products. This research contributes to identify and synthesize findings from various studies that evaluate the effects of fermentation on the quality of the final product using a metabolomics approach, with particular emphasis on metabolic pathways and the metabolites formed. The research highlights that metabolomics, through sophisticated analytical techniques, has successfully identified metabolites produced during fermentation, which are categorized into volatile compounds (such as organic acids, alcohols, and aldehydes) and non-volatile compounds (including polyphenols, amino acids, fatty acids, free sugars, esters, and amides). These compounds play a pivotal role in enhancing the sensory properties of the product and exhibit bioactive potential that can help prevent the development of metabolic diseases, including diabetes, obesity, digestive disorders, and liver cancer. Despite its potential, the metabolomic approach faces challenges due to the large and intricate datasets it produces. Recent technological advancements have led several studies to incorporate Artificial Intelligence (AI) to enhance the accuracy of data derived from metabolite databases. Moreover, integrating other omics disciplines, such as foodomics, is crucial for achieving more detailed research results, encompassing metabolite composition, sensory attributes, and their effects on health. Such integration would contribute to a more holistic understanding and help bridge the gaps in contemporary metabolomic research.